PENGARUH PELATIHAN KERJA DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA KARYAWAN - H, Candra Teguh Setia; Hadi, Lukmono; Suratna, Suratna (Jurnal Ilmu Administrasi dan Bisnis, 2020)
This research was conducted to determine the effect of job training and organizational climate on job satisfaction and its impact on employee performance. This research is an exclusive research with a population of all employees of PT. Hanmi Hair International Banjarnegara, where the sample size in this study was 75 respondents who were determined by proportional unstratifed random sampling. The research data is primary data which is directly collected by a questionnaire. The data analysis technique in this study used descriptive analysis and Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results showed that there was a significant influence between job training on job satisfaction, as well as organizational climate which had a significant effect on job satisfaction. Job training also has a significant effect on employee performance, as well as organizational climate which has a significant effect on employee performance. In addition, job satisfaction has a significant effect on employee performance. Job satisfaction is able to mediate the effect of job training on employee performance and organizational climate on employee performance. Companies in the future need to emphasize training that leads to increasing abilities, directing potential employees to master special skills or to correct deficiencies in carrying out work so that they can productively achieve and realize company goals. A conducive work atmosphere is further enhanced so that employees feel more at home and comfortable in the company.